Preparation, antifungal potentiality, and mechanisms of action of agronanofungicides in controlling rice blast disease and enhancing yield of rice - Kutawa, Abdulaziz Bashir; Ahmad, Khairulmazmi; Hussein, Mohd Zobir; Ali, Asgar; Abdul Wahab, Mohd Aswad; Rafi, Amara; Gunasena, Mahesh Tiran; Mohd Zobir, Syazwan Afif; Berahim, Zulkarami (Springer Nature, 2024)
Pyricularia oryzae is the causative agent of rice blast disease that affects rice yield. The use of chemical fungicides in disease management has generated concern for the environment. In this work, we have developed four agaronanofungicides; chitosan-hexaconazole (CHEN), chitosan-dazomet (CDEN), chitosan-hexaconazole-dazomet (CHDEN), and chitosan agronanofungicide (CEN), and evaluated their antifungal efficacy against P. oryzae. The antifungal effect of the agronanofungicides was studied (in-vitro and in-vivo) by the poisoned media technique, and glasshouse trials. The agronanofungicides significantly inhibited the growth of P. oryzae suppressing the mycelial and conidial growth. The ultrastructural investigations have shown mycelial breakage and damage of the cell membrane in chitosan-based agronanofungicide-treated cells. The results for the efficacy under glasshouse conditions showed that CHDEN was the most promising agronanofungicide in managing rice blast with disease severity index (19.80%), lesion length (1.63 cm), AUDPC (390.60 unit2), disease reduction (80.20%), and a protection index of 82.26%. The least effective fungicide was commercial ANV with a disease severity index of 45.60%, lesion length (3.83 cm), AUDPC (1205.75 unit2), disease reduction (54.40%), and a protection index (45.24%). The treatments of agronanofungicides have increased the yield significantly with CHDEN having 239.00 and the control 113.67 grains per panicle. Based on the harvest index, the CHDEN agronanofungicide treatment had a higher value (0.56) which is significantly different (p ≤ 0.05) while the control had 0.47. This work reveals the strong antifungal effect of CHDEN against P. oryzae and its role in increasing the rice yield. © Koninklijke Nederlandse Planteziektenkundige Vereniging 2024.